Analyzing Students’ Creative Thinking Skills as a Basis for Developing Digital Physics Teaching Materials on Renewable Energy Topics (Jurnal Pendidikan Fisika, 2026)
The rapid advancement of digital technology demands creative, contextual, and sustainability-aligned physics learning. However, high school physics instruction, particularly on renewable energy topics, remains largely conventional and relies on static media, limiting students’ opportunities to develop creative thinking skills. This study aimed to analyze students’ creative thinking skills and learning needs, providing an empirical foundation for the development of contextual, interactive digital physics teaching materials on renewable energy. A descriptive quantitative research design was employed, supported by qualitative data from the teachers’ interviews. The participants consisted of 266 tenth-grade students and three physics teachers from three public senior high schools in Tebo Regency, Indonesia. Data were collected using a 32-item learning-needs questionnaire, a creative thinking skills test based on fluency, flexibility, originality, and elaboration indicators, and semi-structured interviews with teachers. Quantitative data were analyzed using descriptive statistics, and qualitative data were examined through thematic analysis. The results indicate that teacher-centered practices, with limited use of interactive digital media, still dominate physics instruction. Students demonstrated a high demand for contextual, problem-based, and digital learning environments, with an overall learning needs mean score of 82.5%. However, students’ creative thinking skills were generally low, with an average score of 41.8%, particularly in fluency, flexibility, and originality, while elaboration emerged as the relatively strongest indicator. The novelty of this study lies in integrating students’ creative thinking profiles with their learning needs and classroom practices to provide an empirical basis for the instructional design. The findings indicate a significant gap between students’ learning needs and current instructional practices, underscoring the need to develop contextual, interactive digital physics teaching materials. This study contributes to physics education by offering diagnostic evidence to guide the design of digital learning innovations that foster creative thinking and sustainability-oriented understanding.
Keywords: creative thinking skills; digital teaching materials; renewable energy; contextual physics learning; secondary school